Kebiasaan Konsumsi Minuman Remaja untuk Imunitas Tubuh - Rosyanne Kushargina; Wilda Yunieswati; Fauza Rizqiya (Sarana Ilmu Indonesia (salnesia), 2021)
Covid-19 pandemic that is happening in Indonesia and throughout the world has caused changes in people’s eating habits. Food and beverages which can increase immunity become the main focus for the community during this pandemic. This study aimed to analyze the drinking habits on the immunity of SMA Muhammadiyah 25 Pamulang students. This study used a cross-sectional design. There were 78 subjects at the age of 16-17 years old who are 12th grade of SMA Muhammadiyah 25 Pamulang. Drinking habits were collected into 11 beverages types and divided into three categories (1: tea, coffee, and boba drinks; 2: fresh milk, powdered milk, sweetened condensed milk, ice cream containing milk, and yogurt; 3: date juice, honey, and traditional herbal medicine). Data were analyzed descriptively by applying the univariate test method. The results show that 66,67% of subjects consumed boba drinks more often. 32,05% of subjects always consumed coffee, and the last 39,74% of subjects rarely consumed tea. Furthermore, there are 62,82% of subjects more often consume ice cream, 25,64% of subjects constantly consume powdered milk, and 47,44% of subjects rarely consume fresh milk. Hereafter, there are 64,10% of subjects who always consume date juice. subjects often consume honey (47,44%) as well as traditional herbal medicine (46,15%). Subjects drink various beverages such as tea, milk, and their processed products, date juice, honey, and traditional herbal medicine to increase their immunity due to nutrient and antioxidant contents, to protect themselves from virus infection, including Covid-19.